Resistance of a digital voltmeter: teaching creative thinking through an inquiry-based lab. (17th July 2018) - Stojilovic, Nenad; Isaacs, Daniel E
Abstract: We propose an inquiry-based electronics experiment in which students can practice being creative. Through this activity students can learn under what conditions the use of a voltmeter will have measurable effects on the electric circuit and how to design the circuit to measure the internal resistance of the voltmeter.